If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9m-(4m-8)=53)
We move all terms to the left:
9m-(4m-8)-(53))=0
We add all the numbers together, and all the variables
9m-(4m-8)=0
We get rid of parentheses
9m-4m+8=0
We add all the numbers together, and all the variables
5m+8=0
We move all terms containing m to the left, all other terms to the right
5m=-8
m=-8/5
m=-1+3/5
| 3x+6=12+3x | | -2t-2=7t-14-7t | | x/3=5/35 | | 7/4z=42 | | 24=4u+2u | | 16x-7x=81 | | x+3/8=-3 | | 2p+2=63 | | 0=(m+4)(m-4) | | -1+16n=10n-19 | | 7m-20m-10=3 | | (Y-0)=16(x-2) | | 4=z-11/4 | | 10m-2/5=9.60 | | 54+89+x/3=76 | | Y-0=16(x-2) | | 9x=-x+8 | | -13j-12=-12j | | -6t-5=-7t-11 | | 1/2x-2/3=3/4x+1/2 | | -15w=-16-7w | | -15w=-16–7w | | 37+2x=180 | | -16j=-18j+12 | | 54=(4x+6)(2x) | | t+11/2=-4 | | 6x^2-18x-98=0 | | 18n+-11n-18=-3 | | 20+7h=6h | | 3b+5=6b-3b+8-9 | | 5k-10=7k+8 | | -18=-3(h-9) |